KAJIAN IMPLEMENTASI VISITOR MANAGEMENT DI DESA WISATA NGLANGGERAN - Nasir, Syeda Zainab; Shabrina, Yusfi; Nurhidayati, Hindun; Gunadi, I Made Adhi (Kepariwisataan: Jurnal Ilmiah, 2024)
Abstract This research aims to analyze the implementation of visitor management in Nglanggeran Tourism Village. The method in this research refers to a qualitative research method that is descriptive and analytical. Data collection techniques include direct observation, interviews, and literature studies, while data analysis is done through method triangulation. The results showed that the implementation of visitor management in Nglanggeran Tourism Village has been going well, as evidenced by the increase in tariffs for entrance ticket which is effective in controlling the number of tourist visits. In addition, offering various tour packages and tour guide services can optimize the quality of the tourist experience so that it helps achieve tourist satisfaction. However, a clearer limit on the number of visits is needed to anticipate a significant increase in the number of tourist visits in the future, as well as a reference for managers in determining the capacity of the number of visits that can be received at Nglanggeran Tourism Village. This aims to ensure the achievement of tourist satisfaction and the maintenance of safety and comfort for tourists. Keywords: Visitor management; Tourism Village; Quality of Tourist Experience AbstrakPenelitian ini bertujuan untuk menganalisis implementasi visitor management di Desa Wisata Nglanggeran. Metode pada penelitian ini merujuk pada metode penelitian kualitatif yang bersifat deskriptif dan analitis. Teknik pengumpulan data meliputi observasi langsung, wawancara, dan studi literatur, sedangkan analisis data dilakukan melalui triangulasi metode. Hasil penelitian menunjukkan bahwa implementasi visitor management di Desa Wisata Nglanggeran sudah berjalan dengan baik, terbukti dengan adanya kenaikan tarif tiket masuk yang efektif dalam mengendalikan jumlah kunjungan wisatawan. Selain itu, penawaran paket wisata yang beragam serta layanan pemandu wisata dapat mengoptimalkan kualitas pengalaman wisatawan sehingga membantu tercapainya kepuasan wisatawan. Namun, diperlukan pembatasan jumlah kunjungan yang lebih jelas untuk mengantisipasi peningkatan jumlah kunjungan wisatawan secara signifikan di kemudian hari, serta sebagai acuan bagi pengelola dalam menentukan kapasitas jumlah kunjungan  yang dapat diterima di Desa Wisata Nglanggeran. Hal ini bertujuan untuk memastikan tercapainya kepuasan wisatawan dan terjaganya keselamatan dan kenyamanan bagi para wisatawan. Kata Kunci : Visitor management; Desa Wisata; Kualitas Pengalaman Wisatawan